LEARNING FROM PANDEMIC COVID-19 TOWARD AGEING SOCIETIES IN INDONESIA: BUILDING RESILIENCE WITH ADAPTIVE SOCIAL PROTECTION - Seftiani, Sari (Masyarakat Indonesia, 2022)
COVID-19 pandemic reveals how demographic characteristics play an important role to respond the situation that can be useful as a basis of policy making. Demographic aspects associated with the risks of people to expose the Coronavirus. This paper focuses on understanding the COVID-19 pandemic through demographic aspects and how it can be a lesson learned to face the next pandemic in the future, particularly in preparing better approaches towards ageing societies in Indonesia. Using descriptive analyses, data in this paper taken from Statistics Indonesia, Indonesia COVID-19 taskforce, and Social Security Administrator for Health (BPJS Kesehatan). Data reveals that the older a person is, the more vulnerable to have the worse condition when exposed the COVID-19. It is because the increasing of age means the decreasing of physical condition that affect to have chronic diseases which triggers to make the condition becomes worse. The death cases due to COVID-19 are dominated by older people. Almost 50 percent are death on older people who confirmed positive cases. The risk of male to death when exposed by Coronavirus is higher than female. On the other hands, Indonesia is facing the challenge regarding the amount of health workers and bed in the hospital, especially in pandemic situation. In fact, the intensity and frequency of disaster are increasing and at the same time an ageing society lead to the fact that population getting more vulnerable require the comprehensive approach to mitigate and adapt the next disasters. Pandemic COVID-19 becomes a momentum to remind that it is necessary to have better health system and adaptive social protection when the world is getting older.